Indicadores de obesidade: associação com a prevalência, incidência e prognóstico de dor musculoesquelética em participantes da coorte ELSA-BRASIL Musculoesquelético (ELSA-BRASIL MSK), 2012-2019 - Aline Bárbara Pereira Costa (2021)
Obesity and musculoskeletal (MSK) pain are morbidities that affect a significant and growing number of individuals, negatively impacting their quality of life. Studies show that obese individuals have increased prevalence of MSK pain, but there are few studies evaluating the Brazilian population, the role of prolonged exposure to excess weight and measuring the impact of obesity on the risk and prognosis of MSK pain. Thus, we investigated whether different obesity markers were associated with the prevalence of chronic MSK pain in participants of the Brazilian Longitudinal Study of Adult Health Musculoskeletal (ELSA-Brasil MSK), and subsequently evaluated whether obesity affected the risk and prognosis of frequent knee pain. This work was carried out with baseline data from the ELSA-Brasil MSK cohort and the risk and prognosis assessments were based on data from the annual telephone monitoring of the cohort to identify the occurrence of pain episodes. In the cross-sectional analysis we observed that among the 2,899 participants obesity, defined by either body mass index, waist circumference or waist-to-height ratio, was associated with a higher probability of having chronic MSK pain (OR ranged from 1.32 for abdominal obesity level I to 2.08 for body mass index ≥35 kg/m2), multisite chronic MSK pain (OR ranged from 1.35 for overweight to 3.19 for body mass index ≥35 kg/m2) and generalized chronic MSK pain (ORs ranged from 2.12 for a waist-to-height ratio ≥0.5 to 3.65 for a body mass index ≥35 kg/m2). Concerning the body weight trajectory, both participants who were currently overweight, and those who were overweight at age 20 and currently, were more likely to have all pain phenotypes. In the longitudinal analysis, the 2,644 participants who responded to the four monitoring outcomes telephone interviews were divided into two groups: incidence cohort (1,896 participantes without both frequent and chronic knee pain at baseline) and prognosis cohort (748 participante with frequent pain and/or chronic knee pain at baseline). The results showed that in the incidence cohort obesity increased the risk of having one (OR: 1.63; 95% CI 1.13-2.37) and multiple episodes of frequent knee pain (OR: 2.61; 95% CI 1.71 to 3.97), as well as the risk of having severe (OR: 2.10; 95% CI 1.50-2.95) and nonsevere (OR: 1.72; 95% CI 1.04-2.84) episodes. In the prognostic cohort, obesity was a risk factor only for reporting multiple (OR: 2.54; 95% CI 1.60-4.05) and severe (OR: 2.31; 95% CI 1 .49-3.59) episodes. These results highlight the importance of developing strategies focused at weight management both in the collective and individual scope. Interrupting, or at least slowing down the growth of overweight rates in the population and including the management of obesity in the outpatient follow-up of individuals suffering from MSK pain are important measures to prevent the occurrence of this problem and promote a better prognosis for patients who already live with MSK pain.